Wildlife Photographer of the Year. Portfolio 23 - Cox, Rosamund Kidman (London : Natural History Museum, 2013)
Presenting the year's very best wildlife images, this powerful collection of pictures represents the work of many international photographers, both professionals and amateurs. It comprises all the winning and commended photographs from the Wildlife Photographer of the Year 2013 competition, the most prestigious event of its kind in the world.
Includes index of photographers
Keywords: Wildlife photography -- Awards -- Great Britain; Animals -- Pictorial works; Nature -- Pictorial works